INDICADORES DE RENTABILIDADE DA PRODUÇÃO LEITEIRA NUMA PROPRIEDADE NO MUNICÍPIO DE AQUIDAUANA/MS - SANTOS, M. G. R.; PANDOLFO, J.; VEIGAS, P. T. N.; FERREIRA, R. C.; LIMA, P. G. L.; OLIVEIRA, M. V. M. (ANAIS DO ENIC, 2016)
-